An Early Literacy Program for Young Children with Down Syndrome: Changes Observed over One Year. Issue 2 (June 2016) - Colozzo, Paola; McKeil, Leah; Petersen, Jill M.; Szabo, Amanda
Abstract: Although much individual variability exists, most persons with Down syndrome (DS) experience marked expressive language delays and challenges with speech production, hearing, and verbal memory that may negatively affect literacy development. There is, however, a paucity of research with respect to early intervention literacy programs with this population. The authors describe an early intervention literacy program that used a hybrid approach to reading instruction combining whole‐word (i.e., visual) and analytic (i.e., phonic or sound‐based) reading strategies. They also detail the changes observed in the literacy and language abilities of the participants over 1 year. The participants were 15 English speaking Canadian students with DS aged 3–6 years ( M age 4;11, pretreatment) who took part in a 45‐week program. Weekly individual sessions with a certified teacher were augmented by regular homework. Each student's literacy and language abilities were assessed immediately pretreatment and posttreatment. Measures of letter name identification, letter sound identification, print concepts, and identification of taught sight words showed statistically significant changes. Letter name identification, letter sound identification, and number of sight words read pretreatment were all positively and significantly correlated with gains in word identification. There was also a clear difference regarding how many new sight words students were able to read posttreatment depending on whether they used abstract symbols to communicate (i.e., unprompted spoken words or signs) pretreatment. The authors note that this study provides support for literacy interventions that combine phonological awareness, word analysis, sight word training, and shared book reading with children with DS as young as 3 years of age with varying levels of language development.